Gending Aesthetics in Janger Menyali Dance in Sawan District, Buleleng Regency - Ketut Tara Listiawan; Ni Luh Sustiawati; I Ketut Sariada (Journal of Aesthetics, Creativity and Art Management, 2023)
Janger dance is a variety of Balinese art which is classified as a type of social dance for young people in the form of groups (between 16-20 people), very popular among Balinese people. During the dance, groups of female dancers (janger) and groups of male dancers (kecak) dance and sing in unison (mutual sinawurin) with humorous and sometimes romantic songs. The gamelan that is usually used to accompany the Janger dance is called Batel (Tetamburan) which is equipped with a pair of gender puppets. The dance moves are still based on the aesthetic principles of Balinese dance, and the clothing uses the typical janger. Janger dance can adapt to contemporary developments, so janger activists have the freedom to interpret its form, melodies with song lyrics, musical accompaniment, and choreography. In the Janger Menyali dance, the uniqueness of this dance is in terms of the clothes that look quirky, resembling the clothes of the Dutch soldiers when they docked at the Buleleng customs, and the name for the dancers, namely for male dancers it is called jipak, while for female dancers it is called parik. In this study, it is more specific to the aesthetics of gending in the Janger Menyali dance regarding the two pieces that must be performed, namely Dewa Ayu Janger and Mepamit Ring Ratu Gusti Ayu which have the meaning of inviting Dewa Ayu Janger to attend the performance and returning Dewa Ayu Janger to return to his stana with the use of sekar alit banten properties and also kuwud mepayas.